(3TQM GdcGajIs - (3TgGH GdOjf CMeO Hf YeQ (B((3TeS GdOjf(B) (3GdOhdI BHGOj GdgfOjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3eOjfI COQfI s)
(3ChdgG (B:s
(3hHYO, abO Ufa WHbGJ GdCOHGA hGdcJGH JUGfja aj Yde GdEYQGH s
(3BNQgG (B:s
(3Ke NJe HMK Gdfhf HGfbdGHgG GdaGA aj Gdhba hgPG ceG JQi aj HGH MSf GdNJe bO Je Jcejd gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HBNQgG Jedc SfI (B1173(3g`s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs